Selling to the C-suite : what every executive wants you to know about successfully selling to the top - Read, Nicholas A. C.; Bistritz, Stephen J. (McGraw Hill-Ascent Audio, 2018)
THE CLASSIC GUIDE TO HIGH-LEVEL SELLING. Updated with new insights from global executives. How do the best salespeople become trusted advisors to top executives? How do they prepare the right message and get in front of the right influencers and decision-makers? How do they close major sales and establish loyalty for the long-term? The authors of this groundbreaking book took a novel approach to answer these questions by asking more than 500 senior decision-makers what they look for when salespeople call. What these top executives reveal will change the way you sell. This second edition has been updated with new insights on how to stand out and succeed in a market where executives are using social media and other technologies as a key part of their buying process. You'll learn how to:*Target the most relevant executives in any sales opportunity*Win support from the executive's network of gatekeepers and influencers*Position yourself as the supplier who will add the most value with least risk*Update your prospecting and selling skills for the digital age*Sell higher, win bigger, and close faster. Based on the world's largest study of its kind, Selling to the C-Suite, Second Edition blends empirical research with practical insights to help you sell higher, faster, and stronger.